Evaluation of stream visual assessment protocol with measured water quality parameters in urban streams - Caleb McMurray; Abigail C. Finch; Kennedy Jones; Eli Keaton; Hyde Parkinson; Norah Patterson; Jennifer James; JoAnn Burkholder; Ana Meza-Salazar; Erin A. McKenney (PLoS ONE, 2026)
Accurate assessment of stream health is important due to the numerous known influences of habitat, including water quality, on aquatic ecosystems as well as human health. The Stream Visual Assessment Protocol (SVAP) of the Natural Resources Conservation Service is an accessible resource for resource managers and the citizenry that provides a rapid “snapshot” assessment of general stream health, based on visual physical characteristics. This study evaluated whether SVAP scores can be used to infer water quality conditions. We assigned SVAP scores for four urban streams in the southeastern U.S. Piedmont region using ten metrics, and assessed whether the scores were strongly correlated with measured data for four physical features (depth, flow rate, canopy cover, water temperature) and seven water quality parameters (pH, dissolved oxygen concentration and percent saturation, conductivity, total dissolved solids, turbidity, and Enterococcus ). The SVAP scores were strongly correlated with measured physical characteristics, but there were few significant correlations between SVAP scores and water quality data. The findings suggest that the SVAP should not be used to infer water quality conditions, which are critically important to stream habitat health.